Health and Economic Outcomes Among the Alumni of the Wounded Warrior Project : 2013 - Jennifer L. Cerully, Mustafa Oguz (RAND Corporation, 2014)
The nonprofit Wounded Warrior Project (WWP) offers support for and raises public awareness of service members who have experienced physical or mental health conditions associated with their service on or after September 11, 2001. Since 2002, the organization has strived toward supporting Wounded Warriors through three strategic objectives: 1. Ensure that Wounded Warriors are well adjusted in mind and spirit. 2. Ensure that Wounded Warriors are well adjusted in body. 3. Ensure that Wounded Warriors are economically empowered. Each year, WWP conducts an annual assessment of its members (known as alumni), to understand how well its programs and services are achieving the three objectives—that is, supporting the mental, physical, and financial well-being of alumni. The survey administrator, Westat, makes general survey results available to WWP in an initial report. After the initial Westat results were presented to WWP, the organization, as well as its Physical Health and Wellness Program staff and Policy and Government Affairs team, asked RAND to offer an additional interpretation of survey results to supplement those by Westat. This report documents RAND’s supplemental analysis.